Suffix word formation of Belarusian philosophical and sociological terms - Hul, Maryia U. (Journal of the Belarusian State University. Philology, 2019)
The article dwells on Belarusian philosophical and sociological terminology, the history of its formation, the level of its codification and the ways of derivation. The aim is to reveal the most productive suffix derivation types for Belarusian sociological and philosophical terms. The research materials were derived from lexicographical works from the 1920s up to 2011. The most productive word-formation formants were singled out after the analysis. The productivity of the wordformation suffixes has recently increased due to the general tendency to internationalization. Some terms coined in the 1920s left the active vocabulary of the Belarusian language.
Keywords: derivation type; philosophical terms; productive; productivity; sociological terms; suffix; word-formation formant